Pengaruh Kompetensi Pedagogik, Komitmen Kerja, terhadap Kinerja Guru Sekolah Dasar Negeri di Kota Banda Aceh - Zahara Mustika; Nasrun Nasrun; Yasaratodo Wao (Universitas Negeri Medan, 2021)
This study aims to reveal (1) the effect of pedagogic competence on teacher performance (2) the effect of work commitment on teacher performance. This research was conducted at public elementary schools in the city of Banda Aceh. The study population was all public elementary school teachers in the city of Banda Aceh totaling 481 people. Determination of the sample using the Slovin formula, with a total sample of 218 people. Data were collected using a questionnaire filled out by respondents from the teacher. The research analysis used descriptive analysis and inferential analysis with Path analysis. The results showed that: (1) Pedagogical Competence had a significant and significant influence on Teacher Performance, it was shown that ρ51 = 0.252 (2) Work Commitment had a significant influence on Teacher Performance, it was indicated that ρ52 = 0.566 6) The teacher performance model the findings of this study explained that the increase teacher performance can be done through pedagogic competence, work commitment, which will directly lead to better teacher performance.